2022
DOI: 10.3389/fpls.2021.798119
|View full text |Cite|
|
Sign up to set email alerts
|

Nitrogen Supply Affects Yield and Grain Filling of Maize by Regulating Starch Metabolizing Enzyme Activities and Endogenous Hormone Contents

Abstract: This study aimed to examine the effect of nitrogen (N) application rate and time on yield, grain filling, starch metabolizing enzymes, and hormones of maize based on a long-term field experiment initiated in 2012. The total N fertilizer dose [(0 (N0), 100 (N1), 200 (N2), and 300 (N3) kg N ha–1] was split into two (T1, one-third at sowing and two-thirds at the six-leaf stage) or three (T2, one-third each at sowing, six-leaf, and eleven-leaf stage) times application. The results showed that the highest yield was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 53 publications
(63 reference statements)
2
14
0
Order By: Relevance
“…In this line, the highest maize yield was obtained with a N rate of 360 kg/ha in early spring planting and 300 kg/ha in late spring sowing (Coelho et al, 2022). Also, similar results were reported by Yue et al (2022) they noticed that more FIGURE 4 | PCA analysis shows the correlations between agronomic traits and NUE traits according to the N fertilization levels and application time over 2 years. Diagrams are defined by the first two axes of the PCA of the different variables (n = 3); Axis1 (64% of variance explained) and Axis2 (26.4% of variance explained), where T 1 (50% of N at each of sowing and 1st irrigation), T 2 (50% of N at each of sowing and 2nd irrigation) and T 3 (50% of N at each of 1st and 2nd irrigation).…”
Section: Discussionsupporting
confidence: 83%
“…In this line, the highest maize yield was obtained with a N rate of 360 kg/ha in early spring planting and 300 kg/ha in late spring sowing (Coelho et al, 2022). Also, similar results were reported by Yue et al (2022) they noticed that more FIGURE 4 | PCA analysis shows the correlations between agronomic traits and NUE traits according to the N fertilization levels and application time over 2 years. Diagrams are defined by the first two axes of the PCA of the different variables (n = 3); Axis1 (64% of variance explained) and Axis2 (26.4% of variance explained), where T 1 (50% of N at each of sowing and 1st irrigation), T 2 (50% of N at each of sowing and 2nd irrigation) and T 3 (50% of N at each of 1st and 2nd irrigation).…”
Section: Discussionsupporting
confidence: 83%
“…The interaction of PBDEs and AATs may facilitate the transport of both amino acids and PBDEs, which leads to double-edged effects of the plant resistance (the positive side) and the bioaccumulation of PBDEs (the negative side). Plant roots initiated a “cry for help” strategy, such as increasing the synthesis of amino acids, to cope with pollutant-induced oxidative stresses. The synthesized amino acids can be transported to shoots through vascular tissues via intercellular movement mediated by AAT carriers such as LHT. ,,, This pathway enables plant shoots to receive the necessary amino acid supply. The high metabolic flux of amino acids in rice plants were proposed to activate these AATs, which can modulate the (un)­loading and localization of amino acids as well as PBDEs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that GBSS, SBE and SSS are key enzymes in starch synthesis [ 39 ] and that changes in the activities of these enzymes could be divided into unimodality and bimodality after nitrogen fertilizer application in different stages [ 23 , 40 ]. Nitrogen fertilizer can alter transcriptional expression of key enzyme genes in crops and key enzyme activities for starch synthesis to increase starch content [ 41 , 42 ]. In this study, key enzyme activity (GBSS, SBE and SSS) and relative expression of key enzyme genes ( NnGBSS , NnSBEI , NnSBEII and NnSSSIV ) under SCU and RCU treatments all changed according to unimodal curves, which was consistent with rice results [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%